Экспериментальное исследование напряженно-деформированного состояния зубчатого гибкого колеса волновой передачи - Ткаченко, Виталий Николаевич; Устиненко, Александр Витальевич; Борисенко, Сергей Викторович (НТУ "ХПИ", 2017)
Для оценки влияния переменной изгибной жесткости и концентрации напряжений на изгибную выносливость гибкого зубчатого колеса волновой передачи при различных геометрических параметрах зубчатого венца были проведены сравнительные испытания гибких колес на изгибную выносливость. Для определения влияния переменной изгибной жесткости на напряжения изгиба испытывались модели зубчатого венца различной геометрии. Анализ результатов испытаний с приведенной методикой теоретических расчетов позволяет определять напряжения с учётом влияния переменной изгибной жесткости и концентрации напряжения при всевозможных вариациях геометрии зубчатого венца.

Experimental study of stress-strain state of the wave transfer. To evaluate the effect of the variable flexural stiffness and stress concentration on flexural endurance of a flexible gear wheel of a wave gear at different geometrical parameters of a gear ring, comparative tests of flexible wheels on flexural endurance were carried out. To determine the influence of the variable flexural stiffness on the bending stress, the model of the ring gear of various geometries was tested. Analysis of the test results with the above method of theoretical calculations allows to determine the stresses taking into account the influence of the variable flexural stiffness and stress concentration with all possible variations in the geometry of the ring gear.
Experimental study of the stress-strain state of a flexible wheel for wave gear
Keywords: волновая зубчатая передача; напряжение изгиба; изгибная выносливость; ГЗК; ВЗП; wave transmission; tension; bending endurance